Application Research of Artificial Intelligence Technology in Chinese Baijiu Brewing - Zhang, Guiyu; Tuo, Xianguo; Tian, Wanchun; Han, Qiang; Tao, Fan (Journal of Vibration Testing and System Dynamics, 2026)
This study first constructed the information system, and monitored the key technical parameters of the brewing process in real time. The neural network was used to construct the fermented grains model, and the online evaluation of the fermentation process was realized according to the real-time fermentation parameters. The intelligent batching system adjusted the ratio of the fermented grains, grains and other materials according to the evaluation result. The robot used infrared thermal imaging technology to perform the steamerfilling operation. The application results showed that the technology had a positive effect on improving the yield and quality of Chinese Baijiu.